If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(3z + 5) = 10 + -2(z + -5) Reorder the terms: 4(5 + 3z) = 10 + -2(z + -5) (5 * 4 + 3z * 4) = 10 + -2(z + -5) (20 + 12z) = 10 + -2(z + -5) Reorder the terms: 20 + 12z = 10 + -2(-5 + z) 20 + 12z = 10 + (-5 * -2 + z * -2) 20 + 12z = 10 + (10 + -2z) Combine like terms: 10 + 10 = 20 20 + 12z = 20 + -2z Add '-20' to each side of the equation. 20 + -20 + 12z = 20 + -20 + -2z Combine like terms: 20 + -20 = 0 0 + 12z = 20 + -20 + -2z 12z = 20 + -20 + -2z Combine like terms: 20 + -20 = 0 12z = 0 + -2z 12z = -2z Solving 12z = -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. 12z + 2z = -2z + 2z Combine like terms: 12z + 2z = 14z 14z = -2z + 2z Combine like terms: -2z + 2z = 0 14z = 0 Divide each side by '14'. z = 0 Simplifying z = 0
| 121^-1/2 | | 426=350t | | 2(1-7y)=4y+3 | | T-5+7+2k-3k=k-8 | | 6y+7=10y-3 | | 462=370x | | (36x^2y^4)^1/2 | | 4(3z-1)-3(z-8)=3(z-1) | | (T-2)/(4-t) | | -9+10x=4x+15 | | 9=12x^2-23x | | -77.08=9.4y | | 2x-1-4=0 | | -0.56m=4.592 | | 2.3x=14.582 | | 2c+4=14 | | 5/6z-100 | | 13-6m=4-6m | | 3^4/5*3^3/x | | 11k=13t-7k/2t | | 6b^2+48b=0 | | -243=-9(10+n) | | 2x-4-(12+4x)=3x | | 3q^2-6q+2=0 | | 24+3y=24+2x | | x/10=1/4 | | 2x=x*2-15 | | 29x=5x+21+3x | | 4.3x+2=-1 | | A-b-5=p | | S^2-6s+4=0 | | (9m+11)(m+9)=79 |